2019
DOI: 10.3390/ijerph16203969
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic and Environmental Factors Related to Spatial Differences in Human Non-Tuberculous Mycobacterial Diseases in the Czech Republic

Abstract: Non-tuberculous mycobacteria (NTM) are ubiquitous environmental bacteria that can induce pulmonary and non-pulmonary diseases in susceptible persons. It is reported that the prevalence of NTM diseases is increasing in developed countries, but this differs by regions and countries. NTM species distribution and the rate of diseases caused by NTM vary widely in the historical territories of Moravia and Silesia (Czech Republic). This epidemiologic study of NTM diseases covers the period 2012–2018, reviews isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 87 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…On the other hand, local risk factors include conditions that cause disruption of the skin barrier and promote NTM colonization (i.e., skin laser cosmetic surgery, LASIK, catheters) or lung disease, such as cystic fibrosis, especially in adolescents, bronchopulmonary aspergillosis or Staphylococcus aureus colonization, bronchiectasis itself, tuberculosis, chronic obstructive pulmonary disease (COPD), asthma, and every condition that alters parenchymal structure and bronchial epithelium integrity (i.e., air pollution in industrial areas causes the production of reactive oxygen species and secondary inflammatory responses in the lung) [9,11,12].…”
Section: Medical History: Which Risk Factors?mentioning
confidence: 99%
“…On the other hand, local risk factors include conditions that cause disruption of the skin barrier and promote NTM colonization (i.e., skin laser cosmetic surgery, LASIK, catheters) or lung disease, such as cystic fibrosis, especially in adolescents, bronchopulmonary aspergillosis or Staphylococcus aureus colonization, bronchiectasis itself, tuberculosis, chronic obstructive pulmonary disease (COPD), asthma, and every condition that alters parenchymal structure and bronchial epithelium integrity (i.e., air pollution in industrial areas causes the production of reactive oxygen species and secondary inflammatory responses in the lung) [9,11,12].…”
Section: Medical History: Which Risk Factors?mentioning
confidence: 99%
“…Living in an urban or in a rural setting has been associated with altered rates and patterns of NTM infection; for example, living in an area of higher population density was associated with M. kansasii infection, whereas M. avium complex has been associated with living in rural areas [9]. A recent epidemiologic study found a correlation between the incidence of NTM-PD and higher air concentration of particulate matter and benzo[a]pyrene, a polycyclic aromatic hydrocarbon, suggesting that airborne pollution in urban and industrial areas represents a potential risk factor for NTM-PD, probably through the production of reactive oxygen species causing airways chronic inflammation and pulmonary tissue damage [10].…”
Section: Behavioural Change and Education In Ntm-pdmentioning
confidence: 99%
“…Infections caused by M. a. are, however, recorded only scarcely. Thus, during the years 2012–2018, M. a. was diagnosed according to American Thoracic Society (ATS) Criteria in only four (1.32%) patients with mycobacterioses [ 9 ]. Nevertheless, in light of the global rise of the mycobacterioses induced by M. a.…”
Section: Introductionmentioning
confidence: 99%